THE DENTIST'S PERSPECTIVE ON PATIENT SAFETY IN BRAZILIAN DENTAL SERVICES: A GADAMERIAN STUDY - Luiza Gulhermina Oliveira Lopes; Alexandre Bulgarelli (International Journal of Health Services Research and Policy, 2025)
The objective is to understand patient safety in dental care from the perspective of primary health care dentists in a public health system. This is a Hermeneutic study based on 16 interviews with dentists in the Brazilian public health service. Data systematization and analysis were conducted using Content Analysis, and interpretation was supported by the theoretical framework of philosopher Hans-Georg Gadamer. Three themes emerged: The subjectivities/personal perspectives of dentists in their dental practice within workplaces and their recognition of vulnerability to potential errors; working in a culture of patient safety involves both the material aspects of infrastructure and human compassion; the multiprofessional work and the presence of a physician in the team result in a safer and more welcoming patient environment. In conclusion, for dentists working in the Brazilian public health services, patient safety is involved in a multi-professional support and is also associated with dentist compassion, teamwork, and the presence of a physician in the work environment.